Missed care and support figures: Preliminary investigation in some surgical ward - Sollami, Alfonso; Begarani, Federica; Marletta, Giuseppe; Romano, Rita (Acta Biomedica Atenei Parmensis, 2023)
Introduction: Missed Nursing care (MNC) is defined as planned care in the patients care process that is omitted or delayed. Despite their importance in Italy, there are just few studies that measure MNC’s prevalence and causes. We are not aware of studies published in literature that have related MNC with the presence or absence of support staff.Objectives: This study’s objective, was to measure nurse’s perception and reasons for missed care in surgical wards with or without Health Care Assistants (HCA), and, to assess whether there is a significant difference between the two groups of nurses.Methodology: A Cross-sectional observational study was conducted through the administration of the “Missed Nursing Care Survey” in the Italian Version to nurses of the wards surveyed.Results: Results have confirmed that the most frequent MNC are hygiene and mobilisation activities as reported in other Italian and foreign studies, with higher frequency in wards without HCAs. Also, the study confirmed other Italian and foreign study results recognising the most significant motivation for MNC’s as the lack of staff and unexpected events.Conclusions: Without wishing to attribute a cause/effect relation, it is interesting to assess the results, which seem to show that the presence of HCAs contributes to reduce the prevalence of missed activities. The lack of staff has revealed higher average of MNC for both groups, which seems to direct our attention not only towards the presence of HCAs but in regards to their inclusion in care activities. It may be necessary to reflect on the priority that nurses give to certain activities.